Optimizing Aceh’s Traditional Institutions to Provide Legal Protection for Children in Legal Conflict - Anggreini, Rini; Budi Bahreisy; Nurmalawaty (Talenta Publisher, Universitas Sumatera Utara, 2024)
Children as the next generation of our nation, play a crucial role in the development and sustainability of a country. Society aspires to have children who are healthy, intelligent, cheerful, and assured of their survival and growth. However, the social reality often tells a different story, as many children must navigate the legal system for various reasons. Law Number 11 of 2012, concerning the Juvenile Criminal Justice System, introduces the concept of diversion. This concept aims to protect Children in Legal Conflict by shifting the resolution of their cases from the judicial process to an alternative process outside the criminal justice system. In this juvenile justice framework, Traditional Institutions also play an essential role. The involvement of community leaders in the implementation of the diversion agreement demonstrates that